Optical emission spectroscopy of pulsed plasma streams emitted from a modified PF-1000 facility - Skladnik-Sadowska, E.; Kwiatkowski, R.; Malinowski, K.; Sadowski, M.J.; Kubkowska, M.; Paduch, M.; Scholz, M.; Zielinska, E. (Вопросы атомной науки и техники, 2012)
The paper presents results of the recent spectroscopic studies of pulsed plasma streams generated in the PF-1000 facility at the IFPiLM in Warsaw. This facility has recently been equipped with a modified inner electrode, which had the front copperplate with a central tungsten (W) insert of 50 mm in diameter. Interactions of the collapsing current sheath and electron beams with this insert have changed characteristics of the X-ray and VR emission considerably. New spectroscopic measurements were performed at the chosen angle and perpendicular to the discharge axis. In the second case optical emission spectra were recorded at different distances from the electrode outlets, and at various instants after the current peculiarity (dip). It enabled to determine dynamics of the VR emission in the investigated VR range. Представлены результаты недавних спектроскопических исследований импульсных потоков плазмы, генерируемых установкой ПФ-1000, которая расположена в ИФПиЛМ в Варшаве. Эта установка недавно была оснащена модифицированным внутренним электродом, который имел переднюю медную пластину с центральной вольфрамовой (W) вставкой диаметром 5 мм. Взаимодействие схлопывающейся токовой оболочки и электронных пучков с этой вставкой значительно изменило характеристики рентгеновского и излучения в видимом диапазоне. Новые спектроскопические измерения проводились при выбранном угле и перпендикулярно к оси разряда. Во втором случае оптические спектры излучения были зарегистрированы на разных расстояниях от среза электродов и в различные моменты после токовой особенности осциллограммы тока (провала). Это позволило определить динамику ВИ в исследованном диапазоне. Представлені результати недавніх спектроскопічних досліджень імпульсних потоків плазми, що генеруються установкою ПФ-1000, яка розташована в ІФПіЛМ у Варшаві. Ця установка нещодавно була оснащена модифікованим внутрішнім електродом, який мав передню мідну пластину з центральною вольфрамовою (W) вставкою діаметром 50 мм. Взаємодія оболонки струму, яка схлопується, і електронних пучків з цією вставкою значно змінило характеристики рентгенівського випромінювання у видимому діапазоні. Нові спектроскопічні вимірювання проводилися при заданному куті та перпендикулярно до осі розряду. У другому випадку оптичні спектри випромінювання були зареєстровані на різних відстанях від зрізу електродів, і в різні моменти після особливості осцилограми струму (провалу). Це дозволило визначити динаміку ВВ у дослідженому діапазоні.